HOAX DALAM SEJARAH ISLAM AWAL (KAJIAN KRITIS TENTANG QS. AN-NUR : 11-20) - Irfan Afandi (Ar-Risalah Media Keislaman Pendidikan dan Hukum Islam, 2018)
Rapid technology nowadays in addition to give a positive effect, but also give negative effects namely the easy spread of news hoax. Qur'an as Scripture gives a nice I'itibar in the context of Hadith al-ifki. This article tries to understand the verses in the Qur'an an-Nur: 11-20 in the context of the understanding of the hoax in the history of early Islam. An understanding of these verses is carried out with thematic assisted history-a history that lays out the history of Hadith ifki kebahasan understanding at once from the verses. The results of the analysis of the verses produce that news hoax spread through agent spreaders from people near that do not have complete information. On the other hand, there's always a hoax news kibrahu or intellectual actors regulating the dissemination of news hoax. More than that, the hoax can be ditangkal if the community can play an active role in the participatory cultures through always spread prejudice both to fellow Muslims, produce positive news to berana said no to to spreading the hoax. spreaders hoaxes will get Adzab from Almighty God is good in the world and in the hereafter. Hadith ifki described in these verses is the manifestation of compassion and rahmad Allah to mankind. Allah almighty also accept the repentance of those who want to repent for not spreading the hoax.